1997
DOI: 10.1155/1998/21095
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Migration in Murine Cutaneous Leishmaniasis: Regulation by Tumor Necrosis Factor α Interleukin‐1β, and Macrophage Inflammatory Protein‐1α

Abstract: After intradermal infection of mice with the obligatory intracellular parasite Leishmania major, Langerhans cells (LC) are intimately involved in the induction of the primary T-cell immune response. LC can phagocytose Leishmania and transport ingested parasites from the infected skin to the regional lymph nodes. Since TNFα and IL-1β have been shown to induce LC migration after epicutaneous exposure to skin-sensitizing chemicals, we investigated the involvement of both cytokines in the migration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…In leishmanial infections, for example, LC have been demonstrated to transport parasite Ag from the site of infection (skin) to the draining lymph nodes for primary activation of Leishmania-specific T cells (20). Such skin-penetrating pathogens can activate LC migration to the lymph nodes and may use intracellular replication within LC to evade the host immune response (21,22). Furthermore, it has been suggested that resident LC may participate in the initiation of primary immune response in S. mansoni-infected guinea pigs, although the major APC involved were not the resident epidermal LC but rather blood-derived LC (9,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In leishmanial infections, for example, LC have been demonstrated to transport parasite Ag from the site of infection (skin) to the draining lymph nodes for primary activation of Leishmania-specific T cells (20). Such skin-penetrating pathogens can activate LC migration to the lymph nodes and may use intracellular replication within LC to evade the host immune response (21,22). Furthermore, it has been suggested that resident LC may participate in the initiation of primary immune response in S. mansoni-infected guinea pigs, although the major APC involved were not the resident epidermal LC but rather blood-derived LC (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…Such skin-penetrating pathogens can activate LC migration to the lymph nodes and may use intracellular replication within LC to evade the host immune response (21,22). Furthermore, it has been suggested that resident LC may participate in the initiation of primary immune response in S. mansoni-infected guinea pigs, although the major APC involved were not the resident epidermal LC but rather blood-derived LC (9,21). Moreover, in a model of schistosome infection, it has been demonstrated that LC are retained in the epidermis by a mechanism in which parasite-derived PGD 2 impedes migration of LC (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in vitro infection of murine macrophages with L. major promastigotes rapidly induces expression of several CC chemokines; however, this induction is transient, as it reaches a peak at 2 to 4 h and declines to basal levels by 8 h (39). L. major infection in mice can also trigger the production of inflammatory cytokines, including TNF-␣ by epidermal keratinocytes and IL-1␤ by Langerhans cells in murine epidermis (5,37). These cytokines, in turn, induce the production of additional inflammatory mediators, including chemokines (40).…”
Section: Vol 71 2003 Inflammatory Mediators During L Amazonensis Imentioning
confidence: 99%
“…La acumulación temprana de ARNm de IL-1b luego del estímulo antigénico constituye una de las primeras manifestaciones de la activación de la células de Langerhans; la IL-1b es crítica para la activación del linfocito T pues contribuye en la respuesta y generación de la IL-2 por parte del linfocito T y produce efectos proinflamatorios sobre distintos tipos celulares, como es el caso de las células endoteliales en las cuales la activación induce la expresión de moléculas de adhesión como la molécula de adhesión intercelular 1 (ICAM-1) (83); la IL-1b puede aumentar la proliferación de las células B e incrementar la síntesis de inmunoglobulinas, induce la síntesis adicional de otras citocinas como FNT-α, IL-6, GM-CSF y de otros factores como prostaglandina E1 (PGE 1 ) y leucotrieno B4 (LKT4) (59,84,85).…”
Section: Producción De Citocinasunclassified
“…Sin embargo, la migración de las células de Langerhans infectadas con Leishmania también puede ser modulada por citocinas producidas durante la respuesta inflamatoria tales como el TNF-α que aumenta o favorece la migración de dichas células, o la IL-1b que la disminuye (59). Una vez las células de Langerhans migran desde el sitio de la infección hacia el ganglio linfático, la expresión de antígenos del parásito ocurre en las células de Langerhans pero no en los macrófagos (102).…”
Section: Papel De Las Células De Langerhans En La Infección Por Leishunclassified